Adult learning and social capital in the aboriginal tribes of Taiwan - A case study of Taoyuan County Aboriginal College - Chang, Te-Yu (2010)
Aboriginal colleges have played an important role in the struggle for the achievement of social justice, autonomy, and the implementation of aboriginal adult education policy for the aboriginal people in Taiwan. They have become one of the distinguishing features of lifelong education. This study focused on issues with respect to the adult learning and social capital of Aboriginal colleges in Taiwan. The methodology is based on analysis of the organizational structure of an aboriginal college and its curriculum design, teaching style, and community participation. Findings indicate that Taoyuan County Aboriginal College is mainly based on the aboriginal cultural identity. The college has a strong administrative team, its curriculum design is both ‘from top’ and ‘from bottom’, and all of the public and private sectors are invited to participate in their learning programs. In conclusion, the aboriginal college has many programs which have improved the social capital in the tribe